RESEARCH ON LANDSCAPE CHARACTERISTICS OF CORAL ISLANDS IN THE TRUONG SA ARCHIPELAGO - Tuan, Tran Anh (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents a result of research on the differentiation characteristics of natural conditions and landscape classification of coral islands in the Truong Sa archipelago by integrating data on geology, topography, geomorphology, soil and the surface cover from satellite imagery for establishing the landscape map of Truong Sa island in a large scale of 1:5000 and a typical landscape cross section. The research has identified the landscape in emerged coral islands in the Truong Sa archipelago as landscape type of tropical coral island and they were differentiated into two forms of landscapes: the form on the inside of the embankment and the form on the outside of the embankment. Using the substrate criterion, the form on the inside of the embankment was divided into two area groups: the group of guano soils and the group of coastal primitive sandy soils; the form on the outside of the embankment had three area groups: the seasonal moving sandbanks, the cemented clastic rocks and the coral limestone. The surface cover analyzed from satellite images consisted of four types: woody plants, herbaceous plants, construction land and submerged areas. Based on a combination of two criteria (substrate and surface cover), area groups were divided into 7 different geographical areas. The research results are the scientific basis to assess the targets of economic development, national defense and national sovereignty protection in the Truong Sa archipelago.